Identifikasi Tumbuhan Lumut (Bryophyta) Di Kawasan Ijen Geopark dan Pemanfaatannya Sebagai Sumber Belajar - Sari, Ambarroh Nissrina; Supeno; Wahyuni, Diah (Diklabio: Jurnal Pendidikan dan Pembelajaran Biologi, 2023)
This study aims to determine the species of moss plants and to know the use of popular scientific books. The type of research used is qualitative research with exploratory survey methods. The exploratory survey method is carried out by directly tracing the place and object of research. Sampling used a 2×2m plot mounted on the path where the moss was found. The identification process is carried out by analyzing the documented images, observing the morphology, then comparing it with reference books, scientific articles, and validated websites. The results of this study identified 11 moss samples in 5 different tourist sites. These locations include the Rainbow Forest, Megasari Peak, Blawan Waterfall, Wurung Crater, and Kalipait Waterfall. The most commonly found mosses are the class Bryopsida, while the class that few are found is Jungermaniopsida. The results of the identification of moss plants are used in the form of popular scientific books which are validated by 3 expert validators. Validation was carried out in order to determine the feasibility of this book as a source of learning biology. The average validation value is 84.3% with proper qualifications but requires a little improvement.